2016
DOI: 10.1016/j.cell.2015.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-Kinase Regulates Glycolysis through Mobilization of Aldolase from the Actin Cytoskeleton

Abstract: Summary The Phosphoinositide 3-Kinase (PI3K) pathway regulates multiple steps in glucose metabolism but also cytoskeletal functions, such as cell movement and attachment. Here we show that PI3K directly coordinates glycolysis with cytoskeletal dynamics in an AKT-independent manner. Growth factors or insulin stimulate the PI3K-dependent activation of Rac, leading to disruption of the actin cytoskeleton, release of filamentous actin-bound aldolase A and an increase in aldolase activity. Consistently, PI3K-, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
218
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 318 publications
(230 citation statements)
references
References 38 publications
12
218
0
Order By: Relevance
“…As shown in Fig. 3A and reported earlier (15), glycolysis was only modestly reduced by AKT inhibitor MK2206 (Fig. 3A), whereas PI3K inhibitor BKM120 lowered the glycolytic rate strongly, particularly after mobilization of the glycolytic reserve with oligomycin (Fig.…”
Section: Pi3k Inhibition Causes a Selective Decrease In Nonoxidative mentioning
confidence: 60%
See 2 more Smart Citations
“…As shown in Fig. 3A and reported earlier (15), glycolysis was only modestly reduced by AKT inhibitor MK2206 (Fig. 3A), whereas PI3K inhibitor BKM120 lowered the glycolytic rate strongly, particularly after mobilization of the glycolytic reserve with oligomycin (Fig.…”
Section: Pi3k Inhibition Causes a Selective Decrease In Nonoxidative mentioning
confidence: 60%
“…We have recently shown that PI3K directly coordinates glycolysis with cytoskeletal dynamics: PI3K-dependent activation of the GTPase Rac leads to an increased turnover of the actin cytoskeleton with release of the F-actin-bound glycolytic enzyme aldolase A into the cytoplasm where it is enzymatically active. Consistently, inhibitors of PI3K, but not inhibitors of the protein kinase AKT, SGK (serum/ glucocorticoid regulated kinase), or mechanistic target of rapamycin (mTOR), cause a significant decrease in glycolysis at the step catalyzed by aldolase A, whereas activating PIK3CA mutations have the opposite effect (15). A product of the aldolase reaction is the triose glyceraldehyde 3-phosphate (Ga3P), which is a substrate for transketolase (TKT).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, it should be noted that the enzymatic assay disrupts cellular structure and therefore does not detect the regulation of enzymatic activity according to cellular localization. This is important because some glycolytic enzymes, including Aldoa, are localized to specific cellular compartments in addition to the cytoplasm (Hu et al, 2016;Mamczur et al, 2013), and therefore regulation of the cellular localization of glycolytic enzymes could be one of the mechanisms that regulate glucose metabolism rewiring during CB. Area values were normalized to the amount of protein extracted from the embryos, and the relative ratios to E8.5 embryos are shown.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, oncogenic PI3Kα is thought to promote glycolysis by enabling heightened glucose uptake through regulation of GLUT1/4 protein translation (7) and subsequent plasma membrane translocation (8), as well as regulating metabolite pathways (9,10). However, enhanced glycolysis is also observed in rapidly proliferating cells, which requires increased glucose uptake (11).…”
mentioning
confidence: 99%